14,900 farmers benefited from use of RiceAdvice in Nigeria in 2020 and this is equivalent to $2.8 million of gross revenue - CGIAR Research Program on Rice (2020)
RiceAdvice is a free Android application that provides farm-specific advice on rice management practices to farmers. Impact assessment using randomized control trial in northern Nigeria showed that households who were just given the personalized advice increase their yield by 7% and increase their profit by 10%. On average, personalized advice increases yields without increasing the overall quantity of fertilizer used. In 2020, 14,900 farmers benefited from use of RiceAdvice and this is equivalent to $2.8 million of gross revenue.